2009
DOI: 10.1089/cbr.2009.0627
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and Avidity in Antibody-Based Tumor Targeting

Abstract: Many factors contribute to successful tumor targeting by antibodies. Besides properties of the tumor tissue and general antibody pharmacology, a relationship exists between an antibody and its antigen that can shape penetration, catabolism, specificity, and efficacy. The affinity and avidity of the binding interactions play critical roles in these dynamics. In this work, we review the principles that guide models predicting tumor penetration and cellular internalization while providing a critical overview of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
177
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 34 publications
(52 reference statements)
2
177
0
Order By: Relevance
“…In addition to tumor properties (outlined in next section), penetration of antibodies into tumors can be influenced by factors such as antibody affinity, antigen internalization, and antibody metabolism by the tumor. A number of comprehensive reviews have recently addressed this topic in detail (44)(45)(46)(47). Under nonsteady-state conditions, an inverse relationship between antibody affinity and tumor penetration has been predicted (48).…”
Section: Impact Of Affinity On Antibody Elimination and Distributionmentioning
confidence: 99%
“…In addition to tumor properties (outlined in next section), penetration of antibodies into tumors can be influenced by factors such as antibody affinity, antigen internalization, and antibody metabolism by the tumor. A number of comprehensive reviews have recently addressed this topic in detail (44)(45)(46)(47). Under nonsteady-state conditions, an inverse relationship between antibody affinity and tumor penetration has been predicted (48).…”
Section: Impact Of Affinity On Antibody Elimination and Distributionmentioning
confidence: 99%
“…Although such an exosite still awaits experimental confirmation, it is of note that a similar bi/multivalency is well known to increase the affinity/'avidity' and long-lasting binding of antibodies and of many other biological interactions [56]. This concept is well established in biological therapeutics and is increasingly relied upon to generate highly effective drugs and tracers [57][58][59][60]. An essential feature of the current models …”
mentioning
confidence: 99%
“…Previous studies suggested that the binding affinity for antigen plays a pivotal role in the total concentration and penetration of scFv into tumors (13,14). On the basis of scFv/rGel immunotoxins, we showed that increasing affinity could improve cell-binding ability, internalization efficiency, and autophagic cytotoxicity on Her2/neu-positive cells.…”
Section: Discussionmentioning
confidence: 66%